The Effectiveness of the Ittihadul Mubalighin Program in Developing the Studentsâ€™ Da'wah Potential - Basit, Marwan Abdul; Tazky, Deiva; Uyuni, Yuyun Rohmatul (Atthulab: Islamic Religion Teaching and Learning Journal, 2022)
Among the programs owned by the Daarul Falah Islamic boarding school is the "ittihadul mubalighin" program which focuses on helping students learn together in preaching. For this reason, this study wants to discuss the implementation of the "ittihadul mubalighin" program at the Daarul Falah Islamic boarding school to help proselytizing education by students. The research methodology used is descriptive analysis, which is research that aims to focus on solving problems that exist in the present and have factual problems by explaining everything about ittihadul mubalighin at the Darul Falah Islamic Boarding School. The Ittihadul Mubalighin program is a mandatory program that must be taken by students who live in Daarul Falah Islamic Boarding School. The Ittihadul Mubalighin program is coordinated by the head of the organization's board of trustees who is the ustad of the Tahfihz Al-Quran Daarul Falah Islamic Boarding School.Â  Â  Diantara program yang dimiliki oleh pondok pesantren Daarul Falah adalah program â€œittihadul mubalighinâ€ yang berfokus untuk membantu santri belajar bersama dalam berdakwah. Untuk itu, penelitian ini ingin membahas mengenai pelaksanaan program â€œittihadul mubalighinâ€ pada pondok pesantren Daarul Falah untuk membantu pendidikan dakwah oleh santri. Metodologi penelitian yang digunakan deskriptif analisis, yaitu penelitian yang bertujuan untuk memfokuskan pada pemecahan masalah yang ada pada masa sekarang dan memiliki masalah yang faktual dengan menjelaskan segala sesuatu tentang ittihadul mubalighin di Pondok Pesantren Darul Falah. Program Ittihadul Mubalighin merupakan program wajib yang harus ditempuh oleh santri yang bermukim di Pondok Pesantren Tahfihz Al-Quran Daarul Falah. Program Ittihadul Mubalighin dikoordinir oleh ketua majelis pembina organisasi yang merupakan ustad dari Pondok Pesantren Tahfihz Al-Quran Daarul Falah.